THE INFLUENCE OF THE UZBEK LANGUAGE AMONG THE TURKIC PEOPLES TODAY (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the influence of the Uzbek language among the Turkic peoples, its historical, cultural and social significance. The role of the Uzbek language in the family of Turkic languages, its distribution and interaction with other Turkic languages are examined. The article also discusses the role of Uzbek language in education, culture, business and communication.